Reactive arthritis incidence in a community cohort following a large waterborne campylobacteriosis outbreak in Havelock North, New Zealand. Issue 6 (6th June 2022) - Walker, Tiffany A; Grainger, Rebecca; Quirke, Terence; Roos, Rebekah; Sherwood, Jill; Mackereth, Graham; Kiedrzynski, Tomasz; Eyre, Rachel; Paine, Shevaun; Wood, Tim; Jagroop, Anita; Baker, Michael G; et al.
Abstract : Objectives: In August 2016, Campylobacter spp contaminated an untreated reticulated water supply resulting in a large-scale gastroenteritis outbreak affecting an estimated 8320 people. We aimed to determine the incidence of probable reactive arthritis (ReA) cases in individuals with culture-confirmed campylobacteriosis (CC), self-reported probable campylobacteriosis (PC) and those reporting no diarrhoea (ND). Design: We conducted a retrospective cohort study to identify incidence of probable ReA cases. We identified cases with new ReA symptoms using an adapted acute ReA (AReA) telephone questionnaire. Those reporting ≥1 symptom underwent a telephone interview with the study rheumatologist. Probable ReA was defined as spontaneous onset of pain suggestive of inflammatory arthritis in ≥1 previously asymptomatic joint for ≥3 days occurring ≤12 weeks after outbreak onset. Setting: Population-based epidemiological study in Havelock North, New Zealand. Participants: We enrolled notified CC cases with gastroenteritis symptom onsets 5 August 2016–6 September 2016 and conducted a telephone survey of households supplied by the contaminated water source to enrol PC and ND cases. Results: One hundred and six (47.3%) CC, 47 (32.6%) PC and 113 (34.3%) ND cases completed the AReA telephone questionnaire. Of those reporting ≥1 new ReA symptom, 45 (75.0%) CC, 13 (68.4%) PC and 14 (82.4%) ND cases completed the rheumatologist telephone interview. Nineteen CC, 4 PC and 2 ND cases developed probable ReA, resulting in minimum incidences of 8.5%, 2.8% and 0.6% and maximum incidences of 23.9%, 12.4% and 2.15%. Discussion: We describe high probable ReA incidences among gastroenteritis case types during a very large Campylobacter gastroenteritis outbreak using a resource-efficient method that is feasible to employ in future outbreaks.